P08.11 Chlamydia trachomatis incidence from self-reports and serology by age-period, sex and partner numbers in a birth cohort. (13th September 2015) - Righarts, AA; Dickson, NP; Morgan, J; Horner, P; McClure, M; Wills, GS
Abstract : Background: Better understanding of the epidemiology of Chlamydia trachomatis (CT) would assist in prevention and control, but is hindered by asymptomatic infections and analyses based on people tested for clinical reasons that could differ by age and gender. If improved serological detection of CT infection were available, epidemiological studies could more confidently estimate past exposure. We have explored CT incidence by age period in a cohort study, using a combination of a recently characterised serological assay (with higher sensitivity and high persistence) and self-reports. Methods: Sexual health and behaviour information was collected from a cohort of initially 1, 037 participants born in Dunedin, New Zealand in 1972/3, at regular intervals up to age 38. Sera drawn at ages 26, 32 and 38 were tested for antibodies to CT-specific Pgp3 antigen using a double-antigen sandwich enzyme-linked immunosorbent assay. CT incidence was examined by gender, age and number of partners. Results: By age 38, 31.5% (146/464) women and 21.8% (102/469) men had been seropositive and/or self-reported CT infection. More occurred before age 26 than in the 12-year period 26–38 years, the difference being more marked in women than men. In all age periods the risk of acquiring CT increased with number of partners. Once the age-period specific incidence rates were adjusted for the number of partners there was no relationship between CT risk and age period. Overall the partner number adjusted risk was lower in men, although this may reflect that men are less likely to seroconvert than women. Conclusions: CT infection was very common amongst this cohort by age 38. Adjusted analyses showed a major risk factor was number of partners, with no interaction by age-period. The increased risk in men must be interpreted cautiously due to the known difference in serological responses between men and women. Disclosure of interest statement: This study was funded by Health Research Council of New Zealand. No pharmaceutical grants were received in the development of this study.